2010
DOI: 10.1111/j.1525-1594.2009.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel Strategy to Engineer Trachea Cartilage Graft With Marrow Mesenchymal Stem Cell Macroaggregate and Hydrolyzable Scaffold

Abstract: Limited donor sites of cartilage and dedifferentiation of chondrocytes during expansion, low tissue reconstruction efficiency, and uncontrollable immune reactions to foreign materials are the main obstacles to overcome before cartilage tissue engineering can be widely used in the clinic. In the current study, we developed a novel strategy to fabricate tissue-engineered trachea cartilage grafts using marrow mesenchymal stem cell (MSC) macroaggregates and hydrolyzable scaffold of polylactic acid-polyglycolic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…More importantly, co-expression of ALDH1A1 and keratocan was found in GFP labeled rASCs respectively, which demonstrated that surviving rASCs differentiated to the keratocyte phenotype. These results are consistent with a recent study by Liu et al in which they injected umbilical MSCs into the corneal stroma of lum-mice and found that these implanted cells assumed a keratocyte-like phenotype after implantation [30]. It has been speculated that complicated local environmental cues in the cornea, including growth factors, extracellular matrix and cell-cell interactions, may modulate the differentiation of stem cells into the keratocyte phenotype.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More importantly, co-expression of ALDH1A1 and keratocan was found in GFP labeled rASCs respectively, which demonstrated that surviving rASCs differentiated to the keratocyte phenotype. These results are consistent with a recent study by Liu et al in which they injected umbilical MSCs into the corneal stroma of lum-mice and found that these implanted cells assumed a keratocyte-like phenotype after implantation [30]. It has been speculated that complicated local environmental cues in the cornea, including growth factors, extracellular matrix and cell-cell interactions, may modulate the differentiation of stem cells into the keratocyte phenotype.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, we developed a method of seeding cells into a degradable scaffold, which could overcome the drawbacks of cell suspension injection. As a commonly used biomaterial, PLGA has been successfully applied in the fabrication of engineered tissue, such as bladder, cartilage and blood vessels [22,29,30]. Gomes et al [31] reported that they reconstructed cornea with tissue-engineered cell sheets composed of human immature dental pulp stem cells (hIDPSC) in a limbal stem cell deficiency rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…Bone marrow-derived populations of MSCs, such as bone marrow-derived chondrocytes, were widely co-cultivated with respiratory epithelial cells to reconstitute artificially fabricated trachea constructs based on synthetic [27], composite [28], or natural decellularized matrixes [3,29]. A tissue-engineered trachea seeded with bone marrow-derived chondrocytes and airway epithelial cells was successfully implanted into a human recipient [3].…”
Section: Introductionmentioning
confidence: 99%
“…To develop a stable and efficient strategy for directing differentiation of stem cells into a chondrogenic lineage, various material design approaches have been investigated (Anderson et al, 2011; Heymer et al, 2009; Lim et al, 2011; Liu et al, 2010a; Park et al, 2011b), including manipulating polymeric substrate properties such as macromer density, supplementing growth and differentiation factors into the polymeric substrate or coating, immobilizing signaling factors on the polymer surface, and making polymer composites.…”
Section: Control Of Cell Differentiation On Polymersmentioning
confidence: 99%
“…For example, TGF-β1 can be encapsulated with adipose-derived stem cells into carrageenan-based hydrogels to enhance chondrogenic differentiation (Rocha et al, 2011). A coupling of TGF-β1 with marrow mesenchymal stem cell macroaggregates in sheet form and wrapped against a PLGA scaffold also forms cartilaginous tissue (Liu et al, 2010a). Another interesting strategy of using TGF-β1 is to incorporate growth factor-loaded PLGA polymer microspheres within hMSC aggregates themselves.…”
Section: Control Of Cell Differentiation On Polymersmentioning
confidence: 99%